2019
DOI: 10.1002/stem.3130
|View full text |Cite
|
Sign up to set email alerts
|

Linc1557 is critical for the initiation of embryonic stem cell differentiation by directly targeting the LIF/STAT3 signaling pathway

Abstract: Embryonic stem cells (ESCs) have self‐renewal and multi‐lineage differentiation potential and perform critical functions in development and biomedicine. Several long noncoding RNAs (lncRNAs) have been reported as key regulators of stem cell pluripotency and differentiation. However, the function and regulatory mechanism of lncRNAs during the initiation of ESC differentiation remains unclear. Here, we found that linc1557 was highly expressed in mouse ESCs and required for the initiation of ESC differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…55 Additionally, increasing evidence has indicated that lncRNA or miRNA activate the LIF/STAT3 pathway to regulate cellular state and function. 57,[60][61][62] The most significant result of this study indicated that lncRNA-412.25 activated the LIF/STAT3 pathway-mediated GCs state by interacting with miR-346 in Hu sheep.…”
Section: Discussionmentioning
confidence: 99%
“…55 Additionally, increasing evidence has indicated that lncRNA or miRNA activate the LIF/STAT3 pathway to regulate cellular state and function. 57,[60][61][62] The most significant result of this study indicated that lncRNA-412.25 activated the LIF/STAT3 pathway-mediated GCs state by interacting with miR-346 in Hu sheep.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA H19 suppresses the differentiation of Th17 cells and proliferation of ESCs through miR-342-3p/IER3 pathway [ 19 ]. Linc1557 inhibits the differentiation of ESCs by regulating the phosphorylation levels of STAT3 and affecting its stability [ 20 ]. However, the roles and mechanisms of lncRNAs regulate the differentiation of ESCs into pacemaker-like cells is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, the leukemia inhibitory factor (LIF)/STAT3 signaling pathway is essential for maintaining the self-renewal and pluripotency of mESCs [ 59 ]. Linc1557 is mainly located in the cytoplasm of mESCs and directly interacts with STAT3 through specific binding sites to regulate the stability of its mRNA, regulating the LIF/STAT3 signaling pathway and promoting the self-renewal of mESCs [ 60 ]. Peptidylprolyl Isomerase E (PPIE) is an RNA-binding protein located in the nucleus of hESCs [ 61 ].…”
Section: The Functions Of Lncrnas and Their Rbps In Stem Cellsmentioning
confidence: 99%